(3HZjI GdfGSc aj CMcGe GdefGScs - (3eMeO Hf CMeO Hf Ydj GdHghJj GdNdhJj GdMfHdj,J (B1088 (3g` s ((3CMeO GdbHSi GdTGaYi s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHg KbJi MeOkG def fWb GddSGf HPcQg JSHjMkG hJgdjdkG hHYO ajbhd eMeO Hf CMeO Hf Ydi GdHghJi GdMfHdi gPG eG ETJOJ Edjg QMGd GdSGdcjf hSejJg HZjg GdfGSc ai CMcGe GdefGSc s
(3BNQgG (B:s
(3hbWH OhGhjf GdCadGc Yjf GdYjf heLeY GdHMQjf GdSQ GdCNai hGdehQO GdCUai Udi Gddg Ydjg hSde JeJ s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B12 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B294s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdESdGejs